Effect of modeled soil drought on lipoxygenase activity in Triticum spelta - Babenko, L.M.; Kosakivska, I.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The effect of a simulated moderate soil drought on the lipoxygenase (LOG) activity of Triticum spelta plants is studied. Three membrane-bound molecular forms of 9-LOG: LOG-1 (pHopt 5.5), LOG-2 (pHopt 5.8), and LOG-3 (pHopt 6.2) are identified in the above-ground part, in the roots — one 9-LOG (pHopt 6.0). It is shown that, under conditions of drought, the activity of LOG-2 and LOG-3 from the above-ground part increased by 120 and 190 %, respectively, whereas an increase in the activity of LOG-1 is less pronounced. The highest increase in the activity is recorded for 9-LOG localized in the root system of plants. The results obtained indirectly indicate that LOG is involved in the formation of a reaction-response in T. spelta plants under soil drought conditions. Differentiated involvement of the molecular forms of LOG in the adaptation of T. spelta plants to the conditions of water deficiency is discussed.